Performance Limits of Luminescent Solar Concentrators Tested with Seed/Quantum-Well Quantum Dots in a Selective-Reflector-Based Optical Cavity - Song, Hyung-Jun; Jeong, Byeong Guk; Lim, Jaehoon; Lee, Doh C.; Bae, Wan Ki; Klimov, Victor I. (AMER CHEMICAL SOC, 2018)
Luminescent solar concentrators (LSCs) can serve as large-area sunlight collectors for photovoltaic devices. An. important LSC characteristic is a concentration factor (C), which is defined as the ratio of the output and the input photon flux densities. This parameter can be also thought of as an effective enlargement factor of a solar cell active area. On the basis of thermodynamic considerations, the C-factor can reach extremely high values that exceed those accessible with traditional concentrating optics. In reality, however, the best reported values of C are around 30. Here we demonstrate that using a new type of high-emissivity quantum dots (QDs) incorporated into a specially designed cavity, we are able to achieve the C of similar to 62 for spectrally integrated emission and similar to 120 for the red portion of the photoluminescence spectrum. The key feature of these QDs is a seed/quantum-well/thick-shell design, which allows for obtaining a high emission quantum yield (>95%) simultaneously with a large LSC quality factor (Q(Lsc) of similar to 100) defined as the ratio of absorption coefficients at the wavelengths of incident and reemitted light. By incorporating the QDs into a specially designed cavity equipped with a top selective reflector (a Bragg mirror or a thin silver film), we are able to effectively recycle reemitted light achieving light trapping coefficients of similar to 85%. The observed performance of these devices is in remarkable agreement with analytical modeling, which allows us to project that the applied approach should allow one to boost the spectrally integrated concentration factors to more than 100 by further improving light trapping and/or increasing Qisc.